Desarrollo de una aplicación web y móvil para la gestión administrativa de la fundación ecuatoriana de bienestar animal (FEBA) del Cantón Pujilí. - Lopez Quispe, Ruben Darío (2021)
The research aimed to develop a web and mobile application for the Administrative Management of Fundación Ecuatoriana de Bienestar Animal (FEBA),, with the use of new technologies, the processes of adoption, rescues, and sales of items will be facilitated, events and display information about the foundation. Through the use of field research techniques such as interviews and surveys, the necessary information will be obtained to understand the problems of the foundation. Through a bibliographic reference it was possible to choose the appropriate tools for the development of the application such as Java, JavaScript, Firebase Database Manager, Android study.